Розробка математичного та алгоритмічного забезпечення інформаційної технології аналізу фінансового стану емітентів - Шматко, Олександр Віталійович; Овечкіна, Л. С. (НТУ "ХПІ", 2014)
Пропонується метод комплексного фінансового аналізу емітента цінних паперів з використанням нечітких уявлень. Виконано огляд найбільш поширених методик аналізу фінансового стану підприємства. Виконано опис програмного забезпечення, що реалізує запропоновану методику.

Method of complex financial analysis of the issuer's securities using fuzzy concepts proposed. Overview of the most common methods of analysis of the financial condition of the company is made. Analysis of existing methods and models for assessing the financial condition of the company held. The main drawbacks of existing methods and models for assessing the financial condition of the company are shown. The main stages of risk assessment described in bankruptcy. The main parameters used in the analysis of complex financial condition of the company are defined. The classification of the risk of bankruptcy of the company performed. Description software that implements the proposed method performed. Developed software that implements the method of complex financial analysis risk of bankruptcy will improve the quality of managerial decisions when choosing investment options.
Development of mathematical and algorithmic support of information technology analysis of the financial condition of the issuer
Keywords: фондовий ринок; ринок цінних паперів; економіка; оцінка фінансового стану; банкрутство; нечіткі уявлення; stock market; bankruptcy; financial condition assessment; fuzzy representation